A 3-8 GHz RF Receiver Front-End for Multi-Band UWB Wireless System - Hsiung, Zi-Hao; Wu, Hui-I; Jou, Christina F. (My University, 2007)
This paper demonstrates a RF receiver front end circuit for multi-band orthogonal frequency division multiple access (MB-OFDM) using standard 0.18um complementery metal oxide semiconductor (CMOS) technology. The receiver front end includes a low-noise amplifier and a down conversion mixer. The proposed LNA uses transistor's intrinsic capacitor Cgd and only one inductor as input matching network to achieve wideband impedance matching. And the proposed mixer uses folded current reused architecture to decrease supply voltage and enhance conversion power gain effectively. This wideband front end circuit achieves 19-21.5 dB of power gain and 4-3-6.2 dB of double-sideband (DSB) noise figure from 3.1GHz to 8 GHz with IF=100 MHz. The simulated core current consumption was 13.1 mA from a 1.5 V supply, with a compact size of 1.16 mm(2).
Keywords: CMOS; Ultra wide-band; mixer; LNA; MB-OFDM; CMOS; Folded Current Reused